Sleep quality and hemoglobin levels in adolescents - Akhiyan Hadi Susanto; Jihan Salsabila; Yulian Wiji Utami (Universitas Muhammadiyah Semarang, 2024)
Hemoglobin levels play an important role in the health status of adolescents. Low hemoglobin levels in the blood can interfere with the growth process, decrease fitness levels, memory and immunity, and concentration levels. It can affect learning ability and academic achievement in adolescents. Sleep quality is thought to be one of the important factors that can affect hemoglobin regulation in the body. The purpose of this study was to determine the relationship between sleep quality and hemoglobin levels in adolescents at SMAS Sunan Kalijaga Jabung Malang Regency. The research method used observational-cross sectional with a total of 56 adolescents with the Multistage Sampling technique. We used the Pittsburgh Sleep Quality Index (PSQI) questionnaire to determine sleep quality and took capillary blood samples to determine hemoglobin levels. The results showed that most adolescents (89.3%) had poor sleep quality and 39.3% of adolescents had low hemoglobin levels. The correlation test used Spearman Rho and the results were p-value = 0.021 and r = -0.308. This means that there is a relationship between sleep quality and hemoglobin levels. Increasing sleep quality affects the regulation of blood hemoglobin levels in adolescents.